EVALUATION ON ANTIOXIDANT ACTIVITY AND ACTIVE COMPONENTS OF TRIGONA ITAMA PROPOLIS EXTRACT AND ITS POTENTIAL AS SARS-CoV2 INFECTION INHIBITORS - Elma Putri Primandasari; Agus Susilo; Khothibul Umam Al Awwaly; Miftakhul Cahyati; Dewi Masyithoh (Fakultas Teknologi Pertanian Universitas Brawijaya, 2023)
Propolis Trigona itama has a blackish brown color and has a bitter taste. Propolis contains immunomodulator, antibacterial, antifungal and antiviral. Efforts made to determine the potential of propolis require an extraction process. The extraction process aims to obtain propolis ready for consumption. Propolis has thermostable properties with a melting point of 60oC – 65oC, so it does not require high temperatures in the extraction process. The extraction process using MAE requires a faster time because the pressure and temperature can be controlled. This study used a factorial completely randomized design with 2 factors with 9 treatments and 3 replications. The data obtained were analyzed by analysis of variant (ANOVA). If there is a difference, it is continued with the DUNCAN multiple distance test. The results of the extraction using the MAE method of propolis have antioxidant activity using the DPPH method of 1,460µg/ml to 1,413 µg/ml which is expressed in IC50. Trigona itama propolis extract had an average antioxidant value of 0.22 µg/ml to 0.57 µg/ml using the FRAP method.There is a unique component in the GCMS results of Trigona itama propolis extract called bisalcofen.Bisalcofen is an active component which has antioxidant properties. The results of the bisalcofen docking score of -7.6 on the ACE2 protein. Bisalcofen has a stronger potency than umifenovir which can be used as an inhibitor of SARS-CoV2 infection.